15. EVALUATION OF ACUTE AND SUBCHRONIC TOXICITY OF TĐĐ-HV HARD CAPSULE EXTRACT IN EXPERIMENTAL ANIMALS. (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the acute and sub-chronic toxicity of TĐĐ-HV hard capsules in experimental animals.Methods: The oral acute toxicity was studied in Swiss mice using the Litchfield–Wilcoxon method. The oral sub-chronic toxicity was assessed in Wistar rats, following the guidelines of the WHO and the Ministry of Health. Results: The LD50 of TĐĐ-HV hard capsules could not be determined and no acute toxicity manifestations were observed in orally administered mice at doses equivalent to 20.83 times the anticipated human therapeutic dose (corresponding to 15.75 g extract/day). Subchronic toxicity: rats administered doses of 378 mg/kg/day and 1134 mg/kg/day showed no statistically significant differences in general condition, hematological, gross anatomical observations, biochemical and histological indices of liver and kidney between control group and 2 groups using drug had no difference (p > 0.05).Conclusion: TĐĐ-HV hard capsules extract does not cause acute toxicity; and is safe at the dose levels used in the 28-day subchronic toxicity evaluation in experimental animals.
Keywords: Hard capsules; TĐĐ-HV; toxicity; experimental; diabetes mellitus